GPS as a Weather Sensor. (24th December 2013) - Kumar, Mohi
Abstract : Global Positioning System (GPS) stations are not just useful for studying how tectonic plates and glaciers surge or creep or how land deforms as magma runs below it. They also are rapidly becoming important sensors for monitoring the terrestrial water cycle (see "Using GPS to study the terrestrial water cycle, " pages 505–506). What is more, they can help study and forecast weather, according to scientists who presented their work at AGU's 2013 Fall Meeting in San Francisco, Calif.